ADHD in Adults A Practical Guide to Evaluation and Management - Surman, Craig B.H. (Current Clinical Psychiatry, 2013)
ADHD in Adults: A Practical Guide to Evaluation and Management is the product of a unique collaboration of international specialists. This volume offers easy-to-read guidance, and includes checklists, rating scales and treatment planning tools. It was designed for a broad audience of caregivers working in diverse settings, including psychiatrists, social workers, primary care physicians, nurse specialists and psychologists. The authors are highly acclaimed clinicians, investigators and educators. They offer step-by-step guidance for implementation of best practices, drawing from clinical research and their experience treating thousands of patients. They cover diagnosis, treatment planning, and state-of-the-art application of pharmacology, psychotherapy, skill-building, family system and environmental interventions for both simple and complex cases. The scales and worksheets in this Guide were developed to efficiently facilitate assessment and management. The Editor is an international leader in the field from the Clinical and Research Program in Adult ADHD at Massachusetts General Hospital (MGH) and Harvard Medical School, which has made pioneering and highly cited contributions to the understanding of ADHD. This Guide is a definitive, indispensable resource for all health providers who wish to optimize their approach to adult patients with ADHD.